A cloud solution for securing medical image storage - Marwan, Mbarek (Array, 2020)
Cloud computing is an easy-to-use, affordable solution to manage and analyze medical data. Therefore, this paradigm has gained wide acceptance in the healthcare sector as a cost-efficient way for a successful Electronic Medical Records (EMR) implementation. Cloud technology is, however, subject to increasing criticism because of the numerous security vulnerabilities. In this regard, we propose a framework to protect confidential data through the development of new security measures, including compression, secret share scheme and XOR operation. The primary objective of the proposal is to achieve the right balance between security and usability. To this aim, we divide an image into several blocks and then encrypt each piece separately with different cryptographic keys. To enhance privacy and performance, we suggest DepSky architecture to keep data on various storage nodes. Simulation experiments have been conducted to prove the effectiveness of the proposed methodology.